The politics of Western water : the congressional career of Wayne Aspinall - Sturgeon, Stephen C. (Stephen Craig), 1967- (University of Arizona Press, 2002)
As the Democratic congressman from Colorado's Fourth District from 1949 to 1973, Wayne Aspinall was an advocate of natural resource development in general and reclamation projects in particular. This book focuses on Aspinall's congressional career to clarify his role in influencing western water policy. Sturgeon provides a detailed account of the political machinations and personal foibles that shaped Aspinall's efforts to implement water reclamation legislation in support of Colorado's Western Slope, along the way shedding new light on familiar water controversies.